2015
DOI: 10.1017/s0033291715002123
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of psychological distress after prison release: implications for mental health service need in ex-prisoners

Abstract: For the majority of prisoners with high to very high psychological distress, distress persists after release. However, contact with mental health services in the community appears low. Further research is required to understand barriers to mental health service access among ex-prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 37 publications
1
41
1
Order By: Relevance
“…Furthermore, SF-6D utility scores were a function of SF-8 survey responses and only around 40% of participants completed each follow-up survey, with loss to follow-up associated with health risk behaviours. 47 In addition, SF-8 survey has not been validated among ex-prisoner/prisoner populations. Therefore, it is not possible to capture the full range of potential health outcomes using the SF-8/QALY approach, and in this context, given the limitations of our health measure, any conclusions must be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SF-6D utility scores were a function of SF-8 survey responses and only around 40% of participants completed each follow-up survey, with loss to follow-up associated with health risk behaviours. 47 In addition, SF-8 survey has not been validated among ex-prisoner/prisoner populations. Therefore, it is not possible to capture the full range of potential health outcomes using the SF-8/QALY approach, and in this context, given the limitations of our health measure, any conclusions must be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Of concern, however, is that two of the above items were considered unmet for a majority of participants in Psychological distress and Safety to others. Prior research indicates that high levels of psychological distress often persist after release from custody (Thomas et al 2016). Further, although a slight majority of participants were receiving assistance for substance abuse problems, a significant minority of participants’ needs were considered to be unmet here.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation for release as part of throughcare includes needs assessment and key elements like health, family, nance, housing and employment [15]. The ndings of this and other studies showed challenges at release that are complex [26,27]. In our ndings there are challenges on a structural and individual level.…”
Section: Discussionmentioning
confidence: 57%